Lexical and sub-lexical reading skills and their correlation to clinical symptoms in young Chinese patients with schizophrenia. Issue 3 (30th December 2015) - Wang, Jiuju; Wang, Pengfei; Xia, Zhichao; Liu, Jin; Quan, Wenxiang; Tian, Ju; Wydell, Taeko N.; Dong, Wentian
Abstract: Patients with schizophrenia often experience severe reading deficits such as oral reading and reading comprehension deficits. However, it is not known whether different types of lexical or sub-lexical components in reading are also impaired. In order to address this issue, the present study had 22 young Chinese patients with schizophrenia and 22 young Chinese normal controls undergo a battery of reading tests, which specifically measures lexical and sub-lexical components of reading in Chinese. The schizophrenic group further underwent Brief Psychiatric Rating Scale (BPRS) in order to ascertain the severity of patients' clinical symptoms. The results showed that compared to the controls, (1) the schizophrenic patients performed significantly poorly in orthographic processing, orthography–phonology mapping, and orthography–semantic mapping tests and further that (2) their performances in orthographic processing, and orthography–semantic mapping skill tests negatively correlated with the BPRS score. Note however that their ability to access their mental lexicon was intact. There is thus a clear need for studies with a larger sample-size and neurobiological measures which would lead to our better understanding of the behavioral as well as the neural relationships between schizophrenic patients, and their reading processing impairments, thus developing effective reading intervention programs for the schizophrenic patients. Highlights: Chinese young patients with schizophrenia perform backward in O, O–P and O–S. Chinese young patients with schizophrenia have an unaffected mental lexicon. Sub-lexical skills are correlated with clinical symptoms in schizophrenia.